Reconstruction of a nail bed with double-layer artificial dermis for a pincer nail: A case report and literature review - Deng, Weicong; Zhou, Zelin; Leng, Bo; Zeng, Xinming; Shen, Zi; Hong, Yongchang (Frontiers in Surgery, 2023)
Background: Pincer nail (PN) is a type of nail deformity. Although it is a minor ailment, it can cause intractable pain, affecting daily work and life. Currently, there is no standard invention for PN. The main purpose of treatment is to correct the curvature of the nail, so we apply double-layer artificial dermis (DLAD), a novel treatment, for PN according to this aim. Case presentation: A 40-year-old man suffering from PN were treated with DLAD. After 1 year of follow-up, the patient's great toenail plate of right foot was completely grown out. His pain was relieved, and the curvature of the toenail was corrected. Conclusion: The innovative method of using DLAD to fill the ingrown nail bed, not only solves the problem of recurrent pincer nail deformity, but also restores the original appearance of the toenail. It suggested that this simple procedure can be widely applied in clinical practice.